Implementasi Anjak Piutang Syariah dan Kesesuaiannya dengan Fatwa DSN-MUI No. 67 Tahun 2008 dan No. 117 Tahun 2018 Serta POJK No. 10 Tahun 2022: Studi Kasus PT Alami Fintek Sharia - Rohman, Moh. Taufik (Jurnal Ilmiah Ekonomi Islam, 2025)
Abstract Sharia factoring is a transfer of settlement of receivables or short-term bills from the party with the debt to another party who then collects the receivables from the debtor or the party appointed by the debtor in accordance with sharia principles. Sharia factoring itself has been used as a peer to peer lending sharia fintech product, also known as invoice financing or factoring financing. This study uses a qualitative research method in the form of a case study with an empirical legal approach using primary data through interviews with PT Alami Fintek Sharia. While secondary data obtained through various sources including; books, journals, archives as well as reports and publications that can be accessed through the website. The results of this study indicate that; First, the provisions for sharia factoring in the fatwa of DSN-MUI use a Wakalah bil Ujrah contract which can be accompanied by bailout funds (qarḍ) and LPBBTI provisions include legal entity provisions, share ownership, operator capital requirements, controlling shareholders, access and use of personal data, sanctions administrative and others. Second, sharia factoring at PT Alami Fintek Sharia is implemented in invoice financing products by fulfilling the provisions of good corporate governance. Third, the implementation of sharia factoring at PT Alami Fintek Sharia is in accordance with fatwa of DSN-MUI No. 67/2008 and No. 117/2018 and POJK No. 10/2022.